Da’wah bil hikmah in Macapat Serat Wulangreh Songs: Analysis of da’wah messages in javanese cultural expressions - Suprihatiningsih Suprihatiningsih; Tri Marhaeni Pudji Astuti; Agustinus Sugeng Priyanto; Sunarto (Faculty of Dakwah and Communication, Walisongo State Islamic University, 2026)
Purpose – The purpose of this study is to explore Da’wah bil hikmah in the macapat poems of Serat Wulangreh by Pakubuwana IV, focusing on four pupuh, namely Dhandhanggula, Gambuh, Asmarandana, and Kinanthi. This study examines how the message of Da’wah is manifested in the form of Javanese cultural expressions that are rich in moral, ethical, and spiritual values. Method - This study uses a descriptive qualitative approach with content analysis. The research population consists of all verses in Serat Wulangreh, totaling 13 pupuh. The research sample is limited to four pupuh that are the focus of this study. The analysis is conducted textually and contextually to interpret the messages of da'wah contained therein. Result – Research shows that Serat Wulangreh contains messages of preaching with wisdom. Pupuh Dhandhanggula advises that the knowledge received should always be based on sharia principles and taught with wisdom. Pupuh Gambuh emphasizes the importance of honesty and the need to choose the right role models. Asmarandana emphasizes the importance of self-control and humility, while Kinanthi conveys a message about living humbly and choosing good company. Implication – This study indicates the importance of the Da’wah bil hikmah approach in conveying the message of Da’wah through local cultural media. This approach allows the message of Da’wah to be conveyed politely, relevantly, and accepted by a community that upholds symbolic expressions and Javanese traditional values Originality/Value - This study provides a new interpretation of Serat Wulangreh from the perspective of Da’wah bil hikmah, which has rarely been specifically examined in Da’wah studies based on classical literary texts. *** Purpose – Tujuan penelitian ini adalah untuk mengeksplorasi Da’wah bil hikmah dalam tembang macapat Serat Wulangreh karya Pakubuwana IV, dengan fokus pada empat pupuh, yaitu Dhandhanggula, Gambuh, Asmarandana dan Kinanthi. Penelitian ini menelaah bagaimana pesan Da’wah diwujudkan dalam bentuk ekspresi budaya Jawa yang sarat nilai moral, etika, dan spiritual. Method - Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan analisis isi (content analysis). Populasi penelitian adalah seluruh bait dalam Serat Wulangreh yang berjumlah 13 pupuh. Sampel penelitian dibatasi empat pupuh yang menjadi fokus. Analisis dilakukan secara tekstual dan kontekstual untuk menafsirkan pesan Da’wah yang terkandung di dalamnya. Hasil – Penelitian menunjukkan bahwa Serat Wulangreh memuat pesan-pesan Da’wah bil hikmah. Pupuh Dhandhanggula memberikan anjuran agar ilmu yang diterima selalu berlandaskan pada dalil syariat serta diajarkan dengan kebijaksanaan. Pupuh Gambuh menegaskan keutamaan kejujuran dan perlunya memilih teladan yang benar. Asmarandana menekankan pentingnya pengendalian diri dan kerendahan hati, Kinanthi memberikan pesan tentang hidup rendah hati dan memilih pergaulan yang baik. Implication – Penelitian ini mengindikasikan pentingnya pendekatan Da’wah bil hikmah dalam menyampaikan pesan Da’wah melalui media budaya lokal. Pendekatan ini memungkinkan pesan Da’wah tersampaikan secara santun, relevan, dan diterima oleh masyarakat yang menjunjung tinggi ekspresi simbolik dan nilai-nilai adat Jawa. Originality/Value - Penelitian ini memberikan pembacaan baru terhadap Serat Wulangreh dari perspektif Da’wah bil hikmah, yang masih jarang dikaji secara khusus dalam studi Da’wah berbasis teks sastra klasik.